The Effectiveness of a Behavioral Program in Reducing the Aggressive Behavior of Children with Mild Mental Disabilities at the Mu'tah Center for Special Education - Sameer Alremawi; Ahmed A. Arabiyat (Health Psychology Research)
The study aimed to identify the effectiveness of a behavioral counseling program's in reducing aggressive behavior among children with mild mental disabilities at the Mu'tah Center for Special Education. The study sample consisted of (10) male and female students with mild mental disabilities, whose ages ranged between (10-14) years. The one group system (the experimental group) was used. The list of aggressive behavior was applied to the study sample in three stages: The first stage was a baseline (pre-test) and lasted a week, and the second stage was a stage after the completion of the application of the guidance program (post-test), where it lasted for six weeks, while the third stage was the (follow-up measurement) phase, which was carried out two months after stopping the implementation of the program, the repetitions of aggressive behavior were counted. The study used the Wilcoxon Matching Pairs Signed test to calculate the differences between the mean of the pre-test scores and the mean of the post/test scores. The study found the following results: There were differences between the study sample members in the two measurements (pre and post) in the relative weight of the study sample and in favor of the post-test, which indicates the effectiveness of the behavioral counseling program. The results also indicate no statistical differences between the study sample members in the two measures (post and follow up), which indicates the continuity of the effectiveness of the behavioral counseling program.